Chlorination‐promoted Transformation of Isolated Pentagon Rule C78 into Fused‐pentagons‐ and Heptagons‐containing Fullerenes. Issue 18 (29th August 2017) - Brotsman, Victor A.; Ignat'eva, Daria V.; Troyanov, Sergey I.
Abstract: Cage transformations in fullerenes are rare phenomena which are still not fully understood. We report the first skeletal transformation of an Isolated‐Pentagon‐Rule (IPR) isomer of C78 fullerene upon high‐temperature chlorination which proceeds by six‐step Stone–Wales rearrangements affording non‐IPR, non‐classical ( NC ) C78 ( NC 2)Cl24 with two cage heptagons, six pairs of fused pentagons, and an unprecedented loop‐like chlorination pattern. The following loss of a C2 unit results in C76 ( NC 3)Cl24 containing three cage heptagons. Abstract : Nonclassical : High‐temperature chlorination of Isolated Pentagon Rule C78 fullerene with SbCl5 results in the isolation of non‐IPR, non‐classical C 2 ‐C78 Cl24 containing 2 heptagons and 14 pentagons in the lens‐like carbon cage (see picture).The reconstruction of the reaction pathway revealed that the six‐step cage transformation occurs circularly via Stone–Wales rearrangements. An additional step of a C2 loss leads to the formation of C76 Cl24 with 3 cage heptagons.